Enhancing Turkey's Growth Prospects by Improving Formal Sector Business Conditions - Gönenç, Rauf (OECD Economics Department Working Papers, 2007)
Turkey's business sector has achieved high growth over the past few years and - on average - has coped well with increased competition. However, some labour-intensive sectors lost competitiveness prior to the currency depreciation in mid-2006 and faced employment losses, raising political pressure for interventionist policies. This paper argues that the government should resist such pressure and instead follow a broad-based strategy to improve framework conditions for firms, irrespective of their size, sector and legal status. Overcoming the duality between the formal and informal sectors should be the central point of this strategy. In particular, the cost of labour should be reduced and regulatory hurdles in labour and product markets should be minimised, to help formal firms to remain competitive and increase employment. This would also make it easier for the many small and medium-sized firms to move into the formal sector, thereby raising productivity through economies of scale. This would increase the growth potential of the whole economy, broaden the tax base and level the playing field for doing business in Turkey, not only for the wide variety of domestic firms but also for foreign investors